The "that's-not-all" compliance-gaining technique: when does it work?. (3rd April 2019) - Lee, Seyoung; Moon, Shin-Il; Feeley, Thomas Hugh
ABSTRACT: The that's-not-all (TNA) compliance-gaining technique offers a product at an initial price and then improves the deal by either lowering the price or adding an extra product before the target responds to the final and adjusted offer. A meta-analysis with 18 comparisons examining the effectiveness of the TNA strategy found that the technique is a reliable method for increasing compliance ( r = .16). Moderator analyses showed that the technique is effective when the purchase of a product is requested, when the price of a product offered in the final request is lower, and when the concession size is not too large. It is argued that the principles of hedonic editing and mindlessness account for the TNA effect.